Pemanfaatan Platform Digital Sebagai Wadah Penyaluran Aspirasi Untuk Layanan Publik Di Kelurahan Karombasan Selatan - Shelly Pandelaki; Joorie Ruru; Jericho Pombengi (JURNAL ADMINISTRASI PUBLIK, 2023)
The purpose of this study is to explain the services provided to the community in the South Karombasan Sub-District in utilizing digital platforms as a forum for channeling community aspirations for public services in the South Karombasan Sub-District. The method used in this research is descriptive qualitative.. The results of this study found that based on the four components put forward by Eggers and Singh regarding the innovation cycle, namely generating ideas, choosing ideas, implementing ideas, they have gone well, but in disseminating ideas, the South Karombasan government rarely implements them, so the use of this digital platform it is still not optimal, the use of digital platforms should help so that people can easily channel their aspirations for public services in the village. So that the use of the WhatsApp group digital platform is not optimal and is rarely used by the people of the South Karombasan Village. Keywords : Digital iPlatforms, Aspirations, Public iServices